Thyroid gland development in rachycentron canadum during early life stages - Otero, Adriana (2014)
The aim of this study was to describe the ontogeny of thyroid follicles in cobia Rachycentron canadum. Larvae were sampled daily (n=15 - 20) from hatching until 15 dah (days after hatching). Following, larvae were sampled every two days by 28 dah; a new sample was taken at 53 dah. The samples were dehydrated, embedded in Paraplast, and sections of 3 µm were dewaxed, rehydrated and stained with HE and PAS. A single follicle was already present 1 dah and three follicles were found 8 dah. The number of follicles increased up to 19 on 53 dah. The diameter of follicles and follicular cell height were lower 1 dah (6.83 ± 1.00 and 4.6 ± 0.01 µm), but increased from 8 dah (24.03 ± 0.46 µm e 6.43 ± 0.46 µm). From 8 dah, the presence of reabsorption vesicles was observed in the colloid and from the 19 dah some follicles did not present colloid. The early thyroid follicle appearance in cobia larvae as well as the high quantity of follicles without colloid and/or with vesicles even after the metamorphosis, might be the explanation of the fast growth of the cobia.